Outcomes of primary total hip arthroplasty using 3D image-based custom stems in unselected patients: a systematic review. Issue 12 (December 2021) - Nogier, Alexis; Tourabaly, Idriss; Ramos-Pascual, Sonia; Müller, Jacobus H.; Saffarini, Mo; Courtin, Cyril
Abstract : To report clinical and radiographic outcomes of primary THA using three-dimensional (3D) image-based custom stems. This systematic review was performed according to PRISMA guidelines and registered with PROSPERO (CRD42020216079). A search was conducted using MEDLINE, Embase and Cochrane. Clinical studies were included if they reported clinical or radiographic outcomes of primary THA using 3D image-based custom stems. Studies were excluded if specific to patients with major hip anatomical deformities, or if not written in English. Fourteen studies were eligible for inclusion (n = 1936 hips). There was considerable heterogeneity in terms of manufacturer, proximal geometry, coating and length of custom stems. Revision rates ranged from 0% to 1% in the short-term, 0% to 20% in the mid-term, and 4% to 10% in the long-term, while complication rates ranged from 3% in the short-term, 0% to 11% in the mid-term and 0% to 4% in the long-term. Post-operative Harris hip scores ranged from 95 to 96 in the short-term, 80 to 99 in the mid-term, and 87 to 94 in the long-term. Radiographic outcomes were reported in eleven studies, although none reported 3D implant sizing or positioning, nor compared planned and postoperative hip architecture. Primary THA using 3D image-based custom stems in unselected patients provides limited but promising clinical and radiographic outcomes. Despite excellent survival, the evidence available in the literature remains insufficient to recommend their routine use. Future studies should specify proximal geometry, length, fixation, material and coating, as well as management of femoral offset and anteversion. The authors propose a classification system to help distinguish between custom stem designs based primarily on their proximal geometry and length. Cite this article: EFORT Open Rev 2021;6:1166-1180. DOI: 10.1302/2058-5241.6.210053